By His Excellency Benning Wentworth, Esq; captain-general, governor and commander in chief, in and over His Majesty's province of New-Hampshire ... : It having been His Majesty's pleasure to signify his commands to me, that his royal proclamation for a public thanksgiving should be solemnized and kept in all His Majesty's colonies in America ... I have therefore thought fit to cause His Majesty's said proclamation to be herewith printed, and to appoint Thursday the thirteenth day of March to be observed and kept as a day of public thanksgiving throughout this province ... Given at Protsmouth the twenty-eighth day of February, one thousand seven hundred and sixty . (Printed by Daniel Fowle, 1760)
February 28, 1760 Proclamation by Governor Benning Wentworth announcing the King's royal proclamation for a day of thanksgiving and establishing March 13th as a day of public thanksgiving to commemorate the British capture of Quebec.